Remote Laboratory Experiments in a Virtual Immersive Learning Environment - Luca Berruti; Franco Davoli; Sandro Zappatore; Gianluca Massei; Amedeo Scarpiello (Advances in Multimedia)
The Virtual Immersive Learning (VIL) test bench implements a virtual collaborative immersive environment, capable of integrating natural contexts and typical gestures, which may occur during traditional lectures, enhanced with advanced experimental sessions. The system architecture is described, along with the motivations, and the most significant choices, both hardware and software, adopted for its implementation. The novelty of the approach essentially relies on its capability of embedding functionalities that stem from various research results (mainly carried out within the VICOM national project), and “putting the pieces together” in a well-integrated framework. These features, along with its high portability, good flexibility, and, above all, low cost, make this approach appropriate for educational and training purposes, mainly concerning measurements on telecommunication systems, at universities and research centers, as well as enterprises. Moreover, the methodology can be employed for remote access to and sharing of costly measurement equipment in many different activities. The immersive characteristics of the framework are illustrated, along with performance measurements related to a specific application.